Dampak Pembelajaran Daring Selama Pandemic Terhadap Kemampuan Kognitif Peserta Didik - Dewi Niswatul Fithriyah; Suttrisno; Nurul Mahruzah Yulia; Fiki Dzakiyyatul Aula (Jurnal Riset Madrasah Ibtidaiyah, 2022)
Lately, we faced with situations that we have never experienced before. Our country has been attacked by a very dangerous virus for humans, the virus called Covid-19. Covid-19 is a virus that can be transmitted from one individual to another in a relatively short time. In order to minimize the spread of COVID-19, various policies have been put in place. The existence of Covid-19, which never end, had impacts on all aspects, such as economic, social, cultural aspects, and education is no exception. In the implementation of education, all levels of educators which were initially carried out by conducting face-to-face learning must now be carried out in a different way, namely online learning. The aims of writing this article is to explain how the impact of online learning on children's cognitive abilities during the covid-19 pandemic. This study was conducted using literature studies from various journals, and scientific writings and field observations during the pandemic. In addition, it is also done by direct participation during the online learning process. The conclusion from this article is that online learning during this pandemic has both positive and negative impacts on students' cognitive abilities.